2017
DOI: 10.1002/nau.23354
|View full text |Cite
|
Sign up to set email alerts
|

Is repeat Botulinum Toxin A injection valuable for neurogenic detrusor overactivity—A systematic review and meta‐analysis

Abstract: Our study demonstrated that repeat BTX-A injections allow sustained improvements in patients with NDO. The rate of AEs was stable and low. However, additional high-quality, large-scale, and long-term trials are necessary to establish the efficacy and safety of ≥5 repeat BTX-A injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…However, we did not fully share their conclusion that “repeat BTX‐A injections allow sustained improvements in patients with NDO.” Indeed, the 39.8% discontinuation rate and 28.9% failure rate they reported at 7 years raise some concerns that should, in our view, draw attention of the neurourological community. Indeed, this report confirms, in the largest cohort to date and with a remarkable methodology, recent findings from smaller series, with long‐term discontinuation rates of up to 45.2% …”
supporting
confidence: 87%
“…However, we did not fully share their conclusion that “repeat BTX‐A injections allow sustained improvements in patients with NDO.” Indeed, the 39.8% discontinuation rate and 28.9% failure rate they reported at 7 years raise some concerns that should, in our view, draw attention of the neurourological community. Indeed, this report confirms, in the largest cohort to date and with a remarkable methodology, recent findings from smaller series, with long‐term discontinuation rates of up to 45.2% …”
supporting
confidence: 87%
“…BoNT use may have a cumulative immunogenic effect over time in patients with lifelong conditions, such as cervical dystonia [13,98], as well as in patients who receive multiple BoNT-A treatments for a range of different indications (both aesthetic and therapeutic) during their lifetime. Both the FDA [22] and the European Medicines Agency (EMEA) [99] recommend evaluating and mitigating adverse immunologically related responses associated with therapeutic protein products and encourage risk reduction.…”
Section: Immunologists' Perspective: Immunogenicity Should Be a Key Factor In Choice Of Bont Therapymentioning
confidence: 99%
“…In 2009, Pannek et al reported an approximate long-term success rate of 74% [ 26 ]. In a recent review [ 27 ], summarizing 18 studies with a total of 1533 patients, discontinuation rates between 12.1 and 45.2% were described. A 10-year observation period in 140 patients showed an estimated 10-year discontinuation-free survival rate of 49.1% [ 13 ] and a discontinuation rate of 40% [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this finding, a gradually decreased therapeutic effect after the 4th BoNT-A injection in SCI/D patients with NDO was reported [ 33 ]. Furthermore, a significant decrease in quality of life in patients who received five or more injections was described [ 27 ].…”
Section: Discussionmentioning
confidence: 99%